Culture, Sex and Religion: a Study of Contract-Marriage in Cisarua and Jakarta - Arivia, Gadis; Boangmanalu, Abby Gina (Jurnal Perempuan, 2015)
This research is about temporary marriage in the areas of Cisarua and Jakarta. The Islamic discourse in the Arabic culture views temporary marriage as positive to avoid promiscuity (zina). This research indicates that the practice of temporary marriage is manipulation of religion and degradation of Indonesian women. The dominance of Arabic culture in Cisarua influenced the subjectivity and sexuality of women in Indonesia. Respect for the identity of Indonesian women have faded because Indonesian cultural values are not upheld, overpowered by Arabic-patriachal culture and the fact that poverty is still an issue. Temporary marriage is basically prostitution legalized under the pretext of religion. Temporary marriage and siri marriage cannot be distinguished because both exploits the female body.